Pilgrimage and Religion: Pilgrim Religiosity on the Ways of St. James - Heiser, Patrick (Religions, 2021)
Pilgrimages on the Ways of St. James are becoming increasingly popular, so the number of pilgrims registered in Santiago de Compostela has been rising continuously for several decades. The large number of pilgrims is accompanied by a variety of motives for a contemporary pilgrimage, whereby religion is only rarely mentioned explicitly. While pilgrimage was originally a purely religious practice, the connection between pilgrimage and religion is less clear nowadays. Therefore, this paper examines whether and in which way religion shows itself in the context of contemporary pilgrimages on the Ways of St. James. For this purpose, 30 in-depth biographical interviews with pilgrims are analyzed from a sociological perspective on religion by using a qualitative content analysis. This analysis reveals that religion is manifested in many ways in the context of contemporary pilgrimages, whereby seven forms of pilgrim religiosity can be distinguished. They have in common that pilgrims shape their pilgrim religiosity individually and self-determined, but in doing so they rely on traditional and institutional forms of religion. Today’s pilgrim religiosity can therefore be understood as an extra-ordinary form of lived religion, whose popularity may be explained by a specific interrelation of individual shaping and institutional assurance of evidence.